The design and use of a data base for the teaching of history at primary school level - Paul, James R M (Rhodes University, Faculty of Education, Department of Education, 1994)
The changes brought about by society's move from an industrial to an information society has brought with it changes in the way that society operates - from the way we do business to the way we entertain ourselves and, increasingly, in the way we educate our children. That the society of tomorrow requires new skills to survive and operate had been, and continues to be, debated in a growing number of books and in the popular media. More and more educationists are calling for schools to 'restructure' so as to be able to provide the skills that this new society requires, especially those related to the management of information. The nature of these skills are discussed, together with the potential provided by information technology, particularly computers, to provide them. The current use of computers in schools is addressed, together with the apparent inability of schools to generate effective change from within using in-service training. The researcher suggests that this makes it imperative that teacher training institutions provide the next generation of teacher-trainees with a thorough understanding of the requirements of an information society and the tools that it uses. The research undertaken attempted to provide final year primary education teacher-trainees with one example of the way in which the electronic database can be used to change the teaching of history. By researching in the field and entering data into a data base, the teacher-trainees were able to look at information in new ways. By selecting and sorting data by different fields, they were able to act as ' true' historians - each interacting with the data in his or her own way to extract knowledge that is arguably unique for each participant. The data base was then used with a class of standard four pupils, with the researcher acting as participant observer. The reactions and responses of the pupils to the data was noted and these are discussed in the results . A non-participant observer, also a primary school history -teacher, provided input with respect to the validity of the learning experience and to act as a control. The research is described, together with the observations of the researcher, teacher-trainees and pupils involved. The observations of the non-participant observer are also discussed. Shortfalls and difficulties encountered are pointed out, and areas for further research suggested.
Keywords: Education -- Data processing; History -- Study and teaching (Elementary) -- Data processing; Computer-assisted instruction